2022
DOI: 10.3390/jrfm15100477
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Connectedness between Green Bonds, Government Bonds, Corporate Bonds and Other Asset Classes: Insights for Portfolio Investors

Abstract: This paper aims to examine the connectedness between green and conventional assets, particularly during the period of economic downturn. Specifically, we examine quantile-based time-varying connectedness between the green bond market and other financial assets using quantile vector autoregression (QVAR) from 9 March 2018 to 10 March 2021. We use daily prices of S&P U.S. Treasury Bond Index, S&P US Aggregate Bond Index, S&P US Treasury Bond Current 10Y Index, S&P 500 Bond Index, S&P 500 Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 31 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…A negative relationship between conventional sovereign bond returns and the YTM of green bonds suggests that green bonds tend to offer higher yields or become relatively more attractive compared to conventional bonds during periods of declining conventional bond returns. For example, Abakah et al (2022) study showed a strong connectedness between green bonds and conventional sovereign bonds, particularly during economic downturns. The connection between conventional and green bonds is multifaceted and influenced by various factors such as the bond rating and issuing currency (González-Fernández and González-Velasco 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A negative relationship between conventional sovereign bond returns and the YTM of green bonds suggests that green bonds tend to offer higher yields or become relatively more attractive compared to conventional bonds during periods of declining conventional bond returns. For example, Abakah et al (2022) study showed a strong connectedness between green bonds and conventional sovereign bonds, particularly during economic downturns. The connection between conventional and green bonds is multifaceted and influenced by various factors such as the bond rating and issuing currency (González-Fernández and González-Velasco 2018).…”
Section: Resultsmentioning
confidence: 99%